Enhancing Love of Homeland in Early Childhood: A P5 Batik Nusantara Case Study - Masykuroh, Khusniyati; Kurnia, Ratih (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) with the theme Batik Nusantara as an effort to instill a love for the homeland in early childhood. Several studies have previously explored the implementation of the in cultivating love of homeland character. However, these studies have not provided their own contribution by focusing specifically on the cultivation of love for the homeland at the early childhood education through the P5 Batik Nusantara. Using a qualitative case study method, the research involved a principal, two teachers, fifteen group B students, and two parents from a kindergarten in Bekasi, West Java. Data were collected through observation, interviews, documentation, and literature review. Analysis followed the Miles and Huberman model: data reduction, data display, and conclusion. Findings show that the implementation of P5 Batik Nusantara was carried out systematically in five stages: introduction, contextualization, action, reflection, and follow-up. The project effectively fostered love for the homeland through contextual learning, exploration of local culture, and active participation from students and parents. The developed dimensions of the Pancasila Student Profile included global diversity, mutual cooperation, and creativity. Assessment results indicated that most students showed expected developmental progress. These findings contribute to national efforts in strengthening early childhood character education through culturally grounded pedagogies. This study recommends replicating the study in multiple PAUD institutions to test scalability. integrating other cultural or local heritage themes within the P5 framework, or longitudinal tracking to assess sustained character development over time.